PENGARUH MODEL PEMBELAJARAN INKUIRI DAN PENGGUNAAN MEDIA BERBASIS KOMPUTER ( CD MOVIE DAN FLASH) TERHADAP KREATIVITAS SISWA MA KELAS XI PADA POKOK BAHASAN KOLOID - Fuadaturrahmah Fuadaturrahmah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The purpose of this study is to reveal the influence of inquiry learning models and the use of computer-based media (movie and flash CDs) on the creativity of class XI MA students on the subject of colloid, this research uses quasi experimental methods by grouping research samples into two group. The two groups are each made into experimental group 1 and experimental group 2. The results of this study are (1) There is an influence of creativity on students' chemistry learning outcomes that are taught by inquiry learning models with computer-based media use (CD Movie and flash) and learning methods conventional with computer-based media (Movie CDs and flash) at the Medan Medan SU IAIN Laboratory. The average creativity of students with inquiry learning models with the use of computer-based media (CD Movie and flash) is 80.77 while the average creativity of students with conventional learning methods with computer-based media (CD Movie and flash) is 79.23. (2) There is a significant interaction (p = 0.048 or p <0.05) between creativity and inquiry learning models and conventional methods with the use of computer-based media (CD Movie and flash) in influencing student chemistry learning outcomes.